MSC exosomes attenuate sterile inflammation and necroptosis associated with TAK1-pJNK-NFKB mediated cardiomyopathy in diabetic ApoE KO mice - Banerjee, Abha; Singla, Dinender K. (Frontiers in Immunology, 2024)
Introduction Diabetes is a debilitating disease that leads to complications like cardiac dysfunction and heart failure. In this study, we investigated the pathophysiology of diabetes-induced cardiac dysfunction in mice with dyslipidemia. We hypothesize diabetes in ApoE knockout (ApoE-/-) mice induces cardiac dysfunction by increasing inflammation and necroptosis. Methods ApoE-/- mice were divided into experimental groups: Control, Streptozotocin (STZ), STZ + MSC-Exo (mesenchymal stem cell-derived exosomes), and STZ+MEF-Exo (Mouse embryonic fibroblast derived exosomes). At Day 42, we assessed cardiac function, collected blood and heart tissues. Heart tissue samples were analyzed for inflammation, necroptosis, signaling mechanism, hypertrophy and adverse structural remodeling using histology, immunohistochemistry, western blotting, RT-PCR, cytokine array and TF array. Results and Discussion STZ treated ApoE-/- mice developed diabetes, with significantly (p<0.05) increased blood glucose and body weight loss. These mice developed cardiac dysfunction with significantly (p<0.05) increased left ventricular internal diameter end diastole and end systole, and decreased ejection fraction, and fractional shortening. We found significant (p<0.05) increased expression of inflammatory cytokines TNF- a, IL-6, IL-1a, IL-33 and decreased IL-10 expression. Diabetic mice also exhibited significantly (p<0.05) increased necroptosis marker expression and infiltration of inflammatory monocytes and macrophages. MSC-Exos treated mice showed recovery of diabetes associated pathologies with significantly reduced blood glucose, recovered body weight, increased IL-10 secretion and M2 polarized macrophages in the heart. These mice showed reduced TAK1-pJNK-NFKB inflammation associated expression and improved cardiac function with significantly reduced cardiac hypertrophy and fibrosis compared to diabetic mice. Treatment with MEF-Exos did not play a significant role in attenuating diabetes-induced cardiomyopathy as these treatment mice presented with cardiac dysfunction and underlying pathologies observed in STZ mice. Conclusion Thus, we conclude that cardiac dysfunction develops in diabetic ApoE-/- mice, arising from inflammation, necroptosis, and adverse tissue remodeling, which is ameliorated by MSC-Exos, a potential therapeutic for diabetes-induced cardiomyopathy.